PENILAIAN UNJUK KERJA DAN PRAKTIK DALAM PEMBELAJARAN PAI - Puspa Rahayu; Ubabuddin Ubabuddin (CV. ADIBA AISHA AMIRA, 2023)
Performance appraisal is an assessment that is carried out by observing the activities of students in doing something. This assessment is suitable for assessing the achievement of competencies that require students to perform certain tasks such as: laboratory practice, prayer practice, OR practice, presentations, discussions, role playing, playing musical instruments, singing, reading poetry/declamation etc. This method of assessment is considered more authentic than the written test because what is assessed reflects the true abilities of the students.Performance appraisal is an assessment that asks students to do an actual task that applies the required knowledge and skills. Performance appraisal is not only designed as an activity but also designed to achieve the expected competencies. So that in making a performance instrument it must contain several things: 1) authentic and interesting, and involve students in the situation; 2) allows individual assessment; and 3) contain clear instructions.